USING YOUTUBE VIDEOS TO ENHANCE STUDENTS’ CREATIVITY ON FLTM CLASS - Ikmal Ikmal; Abdul Halim; Tri Indah Rusli (Metacommunication: Journal of Communication Studies, 2021)
This study aimed to explore deeply about students experience how YouTube video can enhance students’ creativity toward make a good media for teaching in FLTM class. This research was classroom action research, subject of this study is fifth semester English students at class A. The number of students was 25 students with 4 men and 21 women consisting of 10 research subjects. The instrument of this study conducted two different instruments namely Test and Observation Sheet.  The result of this study showed that the level of students’ creativity was improved from test in meeting I to test meeting II with the data analysis from Test and supported with Observation Sheet. The improvement of students’ score on tests meeting I and II was influenced by the situation in the class. Students' need was one of the main factors that can affect student scores to increase the level of creativity toward make a good media. This study really hopped the results of this study can have an impact on both parties, namely teachers and students as reference to provide progress in teaching quality specifically in the FLTM class.